Effects of dhikr spiritual meditation practice on the recovery of drug abuser: a phenomenology study - Rozeeda Kadri (Global Academic Excellence, 2024)
Meditation based intervention such as mindfulness-based therapy, mantra, yoga, Qi Gong and Zen are generally focused on the integration of Buddhism, Hindhuism and Western psychology. However, little is known about Islamic dhikr spiritual meditation. The present article intent to describe the implications of dhikr meditation to recovering drug addicts’ wellbeing and life based on their experiences. Phenomenological qualitative study design was used with face to face and semi structured interview. Six participants were recruited among recovering drug addicts who had been in the Islamic rehabilitation centre and still practising dhikr spiritual meditation. The entire interviews were recorded and transcribed into verbatim. Then, the transcripts were thematic analytically. Four broad domains which spiritual changes, shift of thought, emotional and behavioural transformation were revealed after consistent and prolonged period of continuos dhikr spiritual meditation. Findings revealed that consistent practice of dhikr meditation has give an apparent impact on recovering drug addicts’ cognitive, emotion and behaviour. In conclusion, the individuals’ belief, values, culture, and spiritual paradigm should be addressed by healthcare professional and counselor to develop holistic strategy for drug addiction therapy.